1996
DOI: 10.1093/jn/126.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Soybean Protein Prevents Bone Loss in an Ovariectomized Rat Model of Osteoporosis

Abstract: The purpose of this study was to examine whether soybean protein isolate prevents bone loss induced by ovarian hormone deficiency. Thirty-two 95-d-old Sprague-Dawley rats were randomly assigned to four treatment groups [sham-operated (sham); ovariectomized (ovx); ovx+soybean; ovx + 17 beta-estradiol (E2)] and killed after 30 d. Rats in the sham, ovx and ovx + 17 beta-estradiol groups were fed a casein-based diet, and the soybean group was fed soybean protein isolate instead of casein; the diets were otherwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
215
2
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 455 publications
(243 citation statements)
references
References 25 publications
15
215
2
11
Order By: Relevance
“…Treatment with isoflavone extract at 6.25 g/kg appeared to prevent bone loss in the femur and lumbar vertebra. These results are supported by previous observations of the positive effects of soybean products -such as soybean protein and soy milk powder -on the bone density of female rats, 8,12,13) because these products contained genistein and daidzein. But, the effects of isoflavone on ALP and TRAP activities are not the same as that of estrogen.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Treatment with isoflavone extract at 6.25 g/kg appeared to prevent bone loss in the femur and lumbar vertebra. These results are supported by previous observations of the positive effects of soybean products -such as soybean protein and soy milk powder -on the bone density of female rats, 8,12,13) because these products contained genistein and daidzein. But, the effects of isoflavone on ALP and TRAP activities are not the same as that of estrogen.…”
Section: Discussionsupporting
confidence: 90%
“…24) Our data on uterine weight, bone density, bone calcium, and bone ash weights confirm the observations of other investigators that bone loss in the OVX rat is prevented by estrogen administration, and that estrogen can also suppress the OVX-induced rise in two biochemical makers of bone turnover: serum ALP and TRAP. 9,13) As expected, the femurs and fourth-lumbar vertebral bones of rats in the OVX-C group had lower values for bone density and mineral content than those of in the SHAM group. Treatment with isoflavone extract at 6.25 g/kg appeared to prevent bone loss in the femur and lumbar vertebra.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It has been reported that genistein has stronger estrogen-like effect than the other flavonoids 6) , induce the activation of osteoblasts and increase the bone mass, and said to be effective in improvement and prevention of osteoporosis 8,9) . Soy isoflavones are also highly safe 10,11) because it is a natural ingredient derived from food, so side effects such as osteonecrosis of the jaw caused by osteoporosis bisphosphonate drug therapy has not been reported.…”
Section: Introductionmentioning
confidence: 99%